USING TRANSLATED LOCAL SONGS TO TEACH STUDENTS OF THE ENGLISH VILLAGE OF TEMAJUK (JEELT : JOURNAL OF EDUCATION AND ENGLISH LANGUAGE TEACHING, 2023)
This qualitative research was conducted to analyze and explain an event, phenomenon, social dynamics, or perception of a person or group using regional songs translated into English to teach students in Temajuk village. The subjects of this research were active students in grades IV and V in the English Village, Temajuk Village. The sample was selected using purposive sampling. This research uses data collection techniques, namely field notes and documentation. The results of data analysis show that using translated regional songs to teach English benefits students. They can sing regional songs with a different sensation because they are translated into English, which motivates them to be more active and practice English more often. There are many advantages to teaching English through folk songs, such as classroom activities that are varied, fun, and lively and make young learners active and confident. Then, it can improve young learners' skills in memorizing and pronouncing new words clearly and using folk songs as an activity in teaching English and helping teachers build active and exciting classes.